2016
DOI: 10.1016/j.tibs.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Structures and Functions of Surfactant Proteins

Abstract: Surface tension at liquid–air interfaces is a major barrier that needs to be surmounted by a wide range of organisms; surfactant and interfacially active proteins have evolved for this purpose. Although these proteins are essential for a variety of biological processes, our understanding of how they elicit their function has been limited. However, with the recent determination of high-resolution 3D structures of several examples, we have gained insight into the distinct shapes and mechanisms that have evolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 86 publications
(142 reference statements)
1
19
0
Order By: Relevance
“…S2) that the role for disulfide bond formation in modulating BslA activity is not linked with either protein stability or folding, but is instead associated with imparting new function through multimerization. This function is in contrast to the fungal hydrophobins, where disulfide bonds stabilize the structure of the protein (26), and is more analogous to the mechanism used to control activity of the von Willebrand factor during blood clotting (25). Previous bioinformatic analyses revealed that Firmicutes, including B. subtilis, limit the number of proteins that contain cysteine residues (27).…”
Section: Discussionmentioning
confidence: 99%
“…S2) that the role for disulfide bond formation in modulating BslA activity is not linked with either protein stability or folding, but is instead associated with imparting new function through multimerization. This function is in contrast to the fungal hydrophobins, where disulfide bonds stabilize the structure of the protein (26), and is more analogous to the mechanism used to control activity of the von Willebrand factor during blood clotting (25). Previous bioinformatic analyses revealed that Firmicutes, including B. subtilis, limit the number of proteins that contain cysteine residues (27).…”
Section: Discussionmentioning
confidence: 99%
“…S2) that the role for disulfide bond formation in modulating BslA activity is not linked with either protein stability or folding, but is instead associated with imparting new function through multimerisation. This is in contrast to the fungal hydrophobins where disulfide bonds stabilize the structure of the protein (26) and is more analogous to the mechanism used to control activity of the von Willebrand factor (vWF) during blood clotting (25). Previous bioinformatic analyses reveal that Firmicutes, including B. subtilis, limit the number of proteins that contain cysteine residues (27).…”
Section: Bifunctionality Through Dimerisationmentioning
confidence: 99%
“…Thus, there has been increasing interest in finding organic Pickering particles for both food products and medical applications (Lam et al, 2014, Dickinson, 2010. Alternatives include polymer microgel particles (Matsumiya and Murray, 2016), certain proteins that act almost as Janus particles like fungal (Wang et al, 2013, Burke et al, 2014 and bacterial (Schor et al, 2016) hydrophobins and other polymer particles. Note that all these particles may not be strictly considered as Pickering stabilizers in that they have some degree of flexibility/deformability, though even silica particles have been shown to sinter together on adsorption, leading to so-called armoured bubbles (Abkarian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%